2007
DOI: 10.1021/jp0735886
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Phase Transitions in Phosphatidylcholine Vesicles by Raman Microscopy and Self-Modeling Curve Resolution

Abstract: The study of phospholipid phase transitions is important for understanding drug- and protein-membrane interactions as well as other phenomena such as trans-membrane diffusion and vesicle fusion. A temperature-controlled stage on a confocal Raman microscope has allowed phase transitions in optically trapped phospholipid vesicles to be monitored. Raman spectra were acquired and analyzed using self-modeling curve resolution, a multivariate statistical analysis technique. This method revealed the subtle spectral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
212
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(229 citation statements)
references
References 69 publications
6
212
0
Order By: Relevance
“…DPPC has two completely saturated alkyl chains, and its membrane is in a gel phase at room temperature. 34 Figure 9a shows the FM-CARS spectrum of a thick bulk DPPC film. Note that the CARS spectrum of DPPC membrane can be significantly different from this bulk spectrum.…”
Section: S(ω)mentioning
confidence: 99%
See 2 more Smart Citations
“…DPPC has two completely saturated alkyl chains, and its membrane is in a gel phase at room temperature. 34 Figure 9a shows the FM-CARS spectrum of a thick bulk DPPC film. Note that the CARS spectrum of DPPC membrane can be significantly different from this bulk spectrum.…”
Section: S(ω)mentioning
confidence: 99%
“…In the literature, the 1060 and 1130 cm -1 peaks are assigned to out-of-phase and in-phase C-C stretching vibrations of all-trans conformers, respectively. 32,34 The narrow 1100 cm -1 peak is the C-C stretching mode of conformers with isolated gauche defects. 34,35 Interestingly, we see distinct polarization dependence of CARS images in this frequency region.…”
Section: S(ω)mentioning
confidence: 99%
See 1 more Smart Citation
“…These peaks were assigned as the methylene C-C stretching mode of the trans and gauche conformations in the lipid acyl chains, respectively, and the relative intensity ratio of these peaks are known to be a measure of the ordering of the lipid tails in the liposomes. 29 Unfortunately, most of peaks around 1000 cm -1 had low signal/noise ratio due to the background noise from the silica glass plate used at the bottom of the glass dish, and we could not analyze the changes in peak intensity quantitatively. However, we identified that these peaks shifted to slightly lower wave numbers during the experiments.…”
Section: Results and And And And D D D Discussion Iscussion Iscussionmentioning
confidence: 99%
“…27,41 Several techniques, including variable-temperature infrared and Raman spectroscopy, have been extensively applied in order to monitor the change of the inter-and intramolecular order of lipid molecules during thermal transitions. 27,[41][42][43][44][45][46] In temperature-dependent infrared spectroscopy, the shifts in the vibrational peak positions in the CÀ ÀH stretching region as a function of temperature is utilized to derive the phase transition temperature profiles of PEGylated lipids. Furthermore, the frequencies corresponding to the CÀ ÀH stretching vibrational region (3000-2800 cm 21 ) can be used as indicators of order-disorder transitions of acyl chains because of their strong sensitivities to the conformation of the hydrocarbon chain.…”
Section: Phase Transition Temperature Profiles Of Pegylated Lipidsmentioning
confidence: 99%